Designer Fe3O4@Ag Core–Shell Porous Nanospheres for Enhanced Electromagnetic Interference Shielding of Polymer Nanocomposites. Issue 8 (10th January 2023) - Chakraborty, Indranil; Bose, Suryasarathi; Chatterjee, Kaushik
Abstract : Electromagnetic (EM) pollution is a pressing concern owing to the increasing usage of electronic gadgets. To this end, lightweight and flexible shields are in huge demand to comply with modern electronics, Herein, designer core–shell porous nanospheres (PNSs) are synthesized, and along with multiwalled carbon nanotubes (MWCNTs), their composites are developed in ethylene‐vinyl acetate (EVA) with excellent EM interference (EMI) shielding ability. The Fe3 O4 PNSs synthesized through controlled solvothermal synthesis are systematically evaluated to elucidate the formation of PNSs to attain porous core–shell morphology. The as‐prepared Fe3 O4 PNSs are coated with Ag by electroless deposition. The developed polymer nanocomposite is flexible and lightweight that effectively attenuates the incoming EM radiation with measured shielding effectiveness (SE) up to 29 dB. This work presents novel insights into the evolution of designer PNSs and presents lightweight polymer composites containing the designer PNSs with excellent radiation shielding activity. Abstract : The pathways of incident electromagnetic (EM) waves impact the shielding effectiveness (SE) of ethylene‐vinyl acetate (EVA)‐based polymer nanocomposites containing Fe3 O4 @Ag core–shell porous nanospheres and multiwalled carbon nanotubes (MWCNTs). The developed polymer nanocomposite is lightweight and flexible that effectively attenuates the incoming EM radiation with measured SE up to 29 dB.